Implementation of digital technologies in the silkworm breeding system and their impact on efficiency - Khasanova Raykhon Bozarovna (THE INNOVATION ECONOMY, 2026)
This work highlights the issues of developing innovative activity in the silkworm egg production system, improving existing technological processes, and increasing production efficiency. During the research, the influence of modern breeding achievements, biotechnological methods, digital monitoring systems, and resource-saving technologies on the seed production process was studied. The importance of cooperation between research institutions, farms, and innovation clusters in the production of high-quality silkworm eggs is also substantiated. According to the results of the work, it was established that the introduction of innovative processes in the seed production system serves to increase productivity, reduce the level of morbidity, improve the genetic indicators of offspring, and increase economic efficiency. As a result, proposals and recommendations were developed for improving innovative management mechanisms in the field of silkworm egg production.